ChemInform Abstract: Employing Arynes in Transition‐Metal‐Free Monoarylation of Aromatic Tertiary Amines. Issue 13 (1st April 2014) - Bhojgude, Sachin Suresh; Kaicharla, Trinadh; Biju, Akkattu T.
Abstract A highly monoselective arylation of N, N‐dimethylanilines with in situ generated benzynes without the need of metal catalysts is developed.